A comparative review of the regulation of Islamic banking and finance in Indonesia, Nigeria and the United Kingdom (TEST Trento Student Law Review, 2023)
This study examines the nuances of the regulation of Islamic banking and finance in Nigeria, the UK, and Indonesian jurisdictions, addressing the challenges and prospects for these legal systems and/or economies. The research adopts a qualitative methodology, drawing theory from a vast trove of literature from authors on the African, Asian, and European continents. The basis for bringing this topic into discussion revolves around the undeniable significance that Islamic finance now has in certain parts of the world. Islamic banking dominates the worldwide Islamic finance industry, representing 80% of Islamic finance assets. There is growing concern for the subpar usage of the practice in certain jurisdictions. Most literature does not question this need, perhaps due to the general acceptance of the conventional banking system worldwide. Previous research works are yet to undertake a comparative assessment of the usage of Islamic banking and finance practices among jurisdictions, spanning representative nations from diverse regions and continents, thus occasioning a gap in the literature. This article discusses the legal and regulatory provisions earmarking the practice of Islamic banking and finance in the jurisdictions using available literature. While each jurisdiction recognizes the practice of Islamic finance, those in Indonesia and, to a good extent, the UK, have richer provisions for its development. Thus, while taking cognizance of the social-cultural contexts, a critical assessment of the regulatory mechanisms in Nigeria is carried out against the background provided by the Indonesian and English legal systems. It is found that for there to be a robust appropriation of the practice in the jurisdictions, especially Nigeria, a forward-looking system must be adopted.
Keywords: Islamic banking; Riba; Nigeria; Indonesia; United Kingdom